A new cascade reaction-based colorimetric and fluorescence "turn on" dual-function probe for cyanide and hydrazine detection. (February 2021) - Tang, Lijun; Zhou, Lei; Liu, Aijia; Yan, Xiaomei; Zhong, Keli; Liu, Xiuying; Gao, Xue; Li, Jianrong
Abstract: Selective detection of cyanide (CN − ) and hydrazine (N2 H4 ) are highly desirable owing to the highly toxic properties of these species. We report herein a new cascade reaction-based colorimetric and fluorescence "turn on" dual-function probe (HBTM-HC ) for CN − and N2 H4 detection with long wavelength emission (620 nm) and a large Stokes shift (122 nm). In DMSO/H2 O (3/7, v/v, PBS 10 mM, pH = 9.1) solution, HBTM-HC displays highly selective and sensitive detection of CN − and N2 H4 with the assistance of masking agents (acetone was used to mask N2 H4, and Fe 2+ was used to mask CN − ). The detection limits of HBTM-HC for CN − and N2 H4 were calculated to be 1.38 × 10 −6  M and 5.47 × 10 −6  M, respectively. The sensing mechanisms for CN − and N2 H4 were proved to undergo cascade reactions, which results in deprotection of levulinate group and releasing of compound HBTM . In addition, probe HBTM-HC has been successfully applied to fluorescence imaging of N2 H4 in live MCF-7 cells, detect CN − in sprouting potatoes and apple seeds, and detect CN − and N2 H4 in real water samples with high recovery rates (92.0%–104.5%) and small relative standard deviations (≤7.15%). Graphical abstract: Image 1 Highlights: A cascade reaction-based colorimetric and fluorescence "turn on" probe (HBTM-HC ) has been developed. HBTM-HC displays dual-function recognition for CN − and N2 H4 in an aqueous solution. HBTM-HC can detect CN − and N2 H4 with a long wavelength emission and a large Stokes shift. HBTM-HC is capable of imaging N2 H4 in living MCF-7 cells, detecting CN − in sprouting potatoes and apple seeds. HBTM-HC is applicable to detect N2 H4 and CN − in real water samples.